Molecular Mechanisms of Thyroid Hormone Transport by l-Type Amino Acid Transporter - Krause, Gerd; Hinz, Katrin Manuela (Experimental and Clinical Endocrinology & Diabetes, 2019)
Thyroid hormones (TH) pass through the plasma membrane into the target cells via transporter proteins. Thyroid hormone transporters that have been identified until now belong to two different solute carrier (SLC) subfamilies i) the major facilitator superfamily (MFS) and ii) the amino acid polyamine-organocation (APC) superfamily. Both are comprised by 12 transmembrane helices, however with different structural topology. The TH transporter MCT8, MCT10 and OATP1C1 are members of the MSF. The l-type amino acid transporters (LATs) are transporting neutral amino acids across the membrane. Two LAT subtypes, LAT1 and LAT2 are members of the APC superfamily, need the escort protein 4F2hc and facilitate uptake but no efflux of TH-subtypes. Homology models of LAT2 that are based on crystal structures of APC transporters guided mutagenesis, revealed molecular structure-function determinants for recognition and transition for import and export of TH-subtypes. The recently solved cryo-EM structure of LAT1 confirmed the structural input. Two other LAT subtypes, LAT3 and LAT4 are members of the MFS. From previous observed negative effect of LAT3 and LAT4 on 3,3’-T2 uptake by LAT1 and LAT2 it was indirectly concluded that LAT3 might export 3,3’-T2. There are still open questions that need to be addressed in order to fully understand the molecular recognition pattern and traversing mechanism of import and export of particular TH-subtypes by LAT1 and LAT2. Moreover, clarification is needed whether LAT3 and LAT4 are exporting TH. Recent new data could not verify the initial hypothesis of TH export by LAT3. Therefore, further investigations are necessary to explain the negative effect of LAT3 on the TH import by LAT2.
Keywords: autoimmunity; thyroid; hormones; signal transduction; receptors; thyrotropin; obesity; melanocortin receptors; thyroid hormone transporters; l-type amino acid transporter; uptake/efflux; alimentation; cancer; vitamines; thyroiditis; lymphoma; graves- disease; polycystic ovary syndrome